Analisis dan Perancangan Sistem Informasi Akademik (Studi Kasus SMA Negeri 1 Talang Kelapa Palembang) - Azhar Irfandi; Okta Liansyah; Ervi Cofriyanti; Hermawan Hermawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2014)
Academic information system is a system that provides services such as academic data. In this study, authors take SMA Negeri 1 Talang Kelapa as a research site, because the academic information system at the school has not been managed well,so that it is difficult in implementing the existing academic activities, such as the difficulty of determining the properness criteria for tenth grade students in filtering major social science (IPS) or natural science (IPA), the searching process of student and teacher data still needs a lot of time, consequently the information is difficult to be access quickly, the archival storage need a lot of file cabinet, the student parents are still difficult to know whether their children are present or not, and also the difficulty for seeking information about the student alumni and giving an announcement for the alumni such as high school reunion invitation. Based on those reasons, authors develop a computerized academic information system to resolve the academic problems. The methodology in developing this system is using Rapid Application Development 89nJatisi, Vol. 1 No. 1 September 2014 Title of manuscript is short and clear, implies research results (First Author) Methodology. This methodology has four phases namely requirement phases, in this phase, authors do the observations, interviews and literature study. Second, the design phase, in this phase authors make the data and process model, database design and interface design. The third one, construction phase, in the this phase authors make program codes and the last, implementation phase. in the result of system testing is installed and socialized in the school. By implementation the academic information system, it can help the academic business process in SMA Negeri 1 Talang Kelapa, especially for actualizing the school vision.